A 40-year study of child maltreatment over the early life course predicting psychiatric morbidity, using linked birth cohort and administrative health data: protocol for the Childhood Adversity and Lifetime Morbidity (CALM) study. Issue 2 (7th March 2023) - Kisely, Steve; Leske, Stuart; Arnautovska, Urska; Siskind, Dan; Warren, Nicola; Northwood, Korinne; Suetani, Shuichi; Najman, Jake Moses
Abstract : Background: Child maltreatment is a major public health issue worldwide. Retrospective studies show a strong association between self-reported child maltreatment and poor mental and physical health problems. Prospective studies that use reports to statutory agencies are less common, and comparisons of self- and agency-reported abuse in the same cohort even rarer. Aims: This project will link state-wide administrative health data with prospective birth cohort data ( N = 7223) from Brisbane in Queensland, Australia (including notifications to child protection agencies), to compare psychiatric outcomes in adulthood of agency- and self-reported child maltreatment while minimising attrition bias. Method: We will compare people with all forms of self- and agency-reported child maltreatment to the rest of the cohort, adjusting for confounding in logistic, Cox or multiple regression models based on whether outcomes are categorical or continuous. Outcomes will be hospital admissions, emergency department presentations or community/out-patient contacts for ICD-10 psychiatric diagnoses, suicidal ideation and self-harm as recorded in the relevant administrative databases. Conclusions: This study will track the life course outcomes of adults after having experienced child maltreatment, and so provide an evidence-based understanding of the long-term health and behavioural consequences of child maltreatment. It will also consider health outcomes that are particularly relevant for adolescents and young adults, especially in relation to prospective notifications to statutory agencies. Additionally, it will identify the overlap and differences in outcome for two different sources of child maltreatment identification in the same cohort.